The Role of Quasi-Judicial Authorities in Safeguarding the Rights of Employees Facing Disciplinary Proceedings - Ali , Abdelhamid Ben; Hamadou , Dahmane (Journal of Ecohumanism, 2025)
The exercise of disciplinary authority within the quasi-judicial disciplinary system requires that the appointing authority consult the parity committees, convened as a disciplinary council, before imposing any disciplinary sanction. This is particularly necessary when the hierarchical authority deems that the alleged acts committed by the employee constitute third- or fourth-degree violations of a serious nature. The primary objective behind establishing parity committees and appeals committees is to provide the best possible legal safeguards for employees subject to disciplinary proceedings or sanctions, thereby preventing measures that could jeopardize their professional careers and infringe upon their legally guaranteed rights.